Cigarette Butts Valorization: Activated Hydrochar for Methylene Blue Removal - Phasukarratchai N. (2023)
Cigarette butts (CB) are a toxic waste that is harmful to both environment and health. This research utilized CB as activated carbon (AC) to adsorb methylene blue (MB). The AC production involved the conversion of CB to hydrochar (HC) followed by activation with KOH. The production of HC by hydrothermal carbonization, determined using a central composite robust design (CCRD), was found to be at 200° C for 5.83 h. The AC prepared from HC had a maximal MB adsorption efficiency of 97.49% from an initial MB concentration of 150 mg/L. AC, HC, and CB had significantly different MB removal efficiencies of 97.49%, 7.03% and 6.93%, respectively. The adsorption isotherm of AC with MB fit with Langmuir isotherm absorption which demonstrated that MB is adsorbed on the AC surface by chemical bonding with a single layer. By analyzing the functional groups of organic compounds using FTIR, no carbonyl groups were found in HC which indicates the destructure of cellulose-acetate. Moreover, the weight loss during measured during TGA shows that the mass composition in AC is mostly carbon black. These results show the potential of using AC prepared from waste cigarette butts as an adsorbent to removal color contaminants from water.